Carbon Nitride Aerogels for the Photoredox Conversion of Water. (3rd August 2017) - Ou, Honghui; Yang, Pengju; Lin, Lihua; Anpo, Masakazu; Wang, Xinchen
Abstract: Aerogel structures have attracted increasing research interest in energy storage and conversion owing to their unique structural features, and a variety of materials have been engineered into aerogels, including carbon‐based materials, metal oxides, linear polymers and even metal chalcogenides. However, manufacture of aerogels from nitride‐based materials, particularly the emerging light‐weight carbon nitride (CN) semiconductors is rarely reported. Here, we develop a facile method based on self‐assembly to produce self‐supported CN aerogels, without using any cross‐linking agents. The combination of large surface area, incorporated functional groups and three‐dimensional (3D) network structure, endows the resulting freestanding aerogels with high photocatalytic activity for hydrogen evolution and H2 O2 production under visible light irradiation. This work presents a simple colloid chemistry strategy to construct 3D CN aerogel networks that shows great potential for solar‐to‐chemical energy conversion by artificial photosynthesis.